AB034. Investigation of RNA editing in urinary bladder cancer by transcriptome sequencing analysis - Wu, Song (Transl Androl Urol, 2016)
BACKGROUND: Bladder cancer can be imaged as a sustaining multistage course accumulating genetic and epigenetic changes. Moreover, plenty of studies uncovered that A-to-I RNA editing is an essential part of the growth of normal cells and involved in the variety of biological pathways. To better understand bladder cancer pathogenesis at the molecular level and to uncover novel tumor-initiating events, we integrate RNA-Seq data derived from 15 bladder cancer/normal paired samples. METHODS: Fifteen bladder cancer/normal paired samples are obtained. We conduct transcriptome sequencing and on fifteen pairs of bladder cancer and matched adjacent tissues to identify RNA editing events. RESULTS: Six tumor samples obtained are low-grade bladder cancer (superficial), nine high-grade bladder cancer (invasive). Statistical analyses reveal no significant alterations in the number of editing site between low-grade samples and high-grade samples. Further analysis uncovers that three non-synonymous edits exist in normal samples, and one of them, SON is a normal specific edit. Total 35 non-synonymous edits are identified in all the tumor samples. Further, tumor specific edited gene ANIZ1 is detected in two of the high-grade tumor samples (B59 and B71), suggesting that ANIZ1 may contribute to the progression of urinary bladder cancer. CONCLUSIONS: In this study, 15 bladder cancer/normal paired samples are included to investigate the difference between normal and tumor samples using a revised RNA editing identification method. Multiple RNA editing events are discovered in tumor and normal samples that indicate RNA editing plays a significant role in bladder cancer. Our study is the first one to research RNA editing events at exon genome level in bladder as we are known and it may offer a comprehensive view of the role of RNA editing on bladder cancer.